Electron accepting porphycenes on graphene - Costa, Ruben Dario; Malig, Jenny; Brenner, Wolfgang; Jux, Norbert; Guldi, Dirk Michael (Advanced Materials, 2013)
The versatility of nanographene (NG) as an electron donor is demonstrated when integrated together with an electron accepting porphycene into a novel electron NG hybrid. This feature is further exploited in dye-sensitized solar cells (DSSCs), in which photoanodes (ZnO) reveal a cascade of electron flow as modus operandi. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Integrating metalloporphycenes into p-type NiO-based dye-sensitized solar cells - Feihl, Sebastian; Costa, Ruben D.; Brenner, Wolfgang; Margraf, Johannes; Casillas Pacheco, Ruben; Langmar, Oliver; Browa, Anne; Shubina, Tatyana; Jux, Norbert; Guldi, Dirk Michael; Clark, Timothy (Chemical Communications, 2014)
In the current work, we have explored a novel synthetic route towards metalated porphycenes and their use in p-type NiO-based dye-sensitized solar cells. Particular emphasis is placed on the influence that the relative positioning of the anchoring group exerts on the DSSC performance.

Supramolecular order and structural dynamics: A STM study of 2H-tetraphenylporphycene on Cu(111) - Stark, Michael Werner; Träg, Johannes; Ditze, Stefanie; Brenner, Wolfgang; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Chemical Physics, 2015)
The adsorption of 2H-tetraphenylporphycene (2HTPPc) on Cu(111) was investigated by scanning tunneling microscopy (STM). At medium coverages, supramolecular ordered islands are observed. The individual 2HTPPc molecules appear as two pairs of intense protrusions which are separated by an elongated depression. In the islands, the molecules are organized in rows oriented along one of the close packed Cu(111) substrate rows; the structure is stabilized by T-type interactions of the phenyl substituents of neighboring molecules. Two types of rows are observed, namely, highly ordered rows in which all molecules exhibit the same orientation, and less ordered rows in which the molecules exhibit two perpendicular orientations. Altogether, three different azimuthal orientations of 2HTPPc are observed within one domain, all of them rotated by 15° ± 1° relative to one closed packed Cu direction. The highly ordered rows are always separated by either one or two less ordered rows, with the latter structure being the thermodynamically more stable one. The situation in the islands is highly dynamic, such that molecules in the less ordered rows occasionally change orientation, also complete highly ordered rows can move. The supramolecular order and structural dynamics are discussed on the basis of the specific molecule-substrate and molecule-molecule interactions.

Synthesis and physico-chemical properties of porphycenes - Brenner, Wolfgang; Malig, Jenny; Oelsner, Christian; Guldi, Dirk Michael; Jux, Norbert (Journal of Porphyrins and Phthalocyanines, 2012)
A new and improved synthesis for porphycenes is presented. In particular, treating pyrroles with iodine monochloride results in quantitative yields and easier work up. This key step was employed for the synthesis of different 2,7,12,17-substituted porphycenes (TPrPc, TPPc, TtBPPc). The synthetic part of this project is followed by a global analysis of the physico-chemical properties of three exemplary porphycenes, including absorption, emission, and electrochemistry. In-situ UV-vis/nIR spectroelectrochemistry was used to determine the spectral signatures of the radical anion and cation species. Temperature-dependent fluorescence lifetimes were determined under air as well as under inert atmosphere. © 2012 World Scientific Publishing Company.